Pendidikan Islam perspektif Al-Ghazali: Integrasi Nilai-Nilai Spiritual dan Akhlak Dalam Pembelajaran - Firdasari, Auliya Adiba Rahma; Bakar, M. Yunus Abu (Mahad Aly Al Fithrah, 2025)
This research aims to explore and analyze the concept of Islamic education according to Al-Ghazali, with an emphasis on the integration of spiritual and moral values in the learning process. The main focus of this research is how Islamic education according to Al-Ghazali is a process of forming a perfect human, both in this world and in the afterlife, with the main aim of getting closer (taqarrub) to Allah as the Creator. Al-Ghazali believes that knowledge is a means to achieve human perfection and eternal happiness. According to him, Islamic education must include education in matters of faith, morals, intellectual, social and physical. The ideal teacher must have noble character and apply teaching methods that are oriented towards example, moral development and instilling virtues. This research also highlights that Al-Ghazali had two approaches in designing educational curricula: a tendency towards religion and Sufism, as well as a pragmatic tendency. The integration of spiritual and moral values in the learning process is considered very important to form individuals with noble and devout morals, as well as spreading benevolent values to all mankind.